Gas phase vs. liquid phase: monitoring H2 and CO adsorption phenomena on Pt/Al2O3 by IR spectroscopy. Issue 4 (20th January 2022) - Carosso, Michele; Fovanna, Thibault; Ricchebuono, Alberto; Vottero, Eleonora; Manzoli, Maela; Morandi, Sara; Pellegrini, Riccardo; Piovano, Andrea; Ferri, Davide; Groppo, Elena
Abstract : The adsorption of H2 and CO over Pt/Al2 O3 was studied in gas and in liquid phase by FT-IR and ATR-IR spectroscopies under otherwise similar conditions. The solvent competes with hydrogen and CO for terrace and kink metal sites. Abstract : The adsorption phenomena occurring at the surface of a highly-dispersed Pt/Al2 O3 catalyst for hydrogenation reactions were thoroughly investigated in the gas-phase by transmission IR spectroscopy and in the liquid-phase by ATR-IR spectroscopy. The reduction of Pt/Al2 O3 in H2 with the formation of Pt–hydrides and adsorption of CO were used as case studies for the comparison of the two different environments under otherwise similar experimental conditions. We found that compared to gas-phase, the selected solvent (cyclohexane) greatly affects the reducibility of Pt. Incomplete reduction under the adopted liquid-phase conditions was demonstrated by the formation of carbonate species at very low CO coverage. Moreover, cyclohexane competes with the adsorbates (H2 as well as CO) for the occupancy of the available surface sites, thus affecting the shape, position and relative intensity of the infrared signals corresponding to the surface Pt–H and Pt–CO species and leading to an overall lower H and/or CO coverage. Our spectroscopic data show also that the presence of the solvent is crucial in maintaining the Pt nanoparticles in partially H-solvated state even in a H2 -free environment. This evidence might have important implications with respect to the catalyst reactivity and stability.